Efektivitas Konseling Kelompok dengan Teknik Charting Irrational Beliefs untuk Meningkatkan Kesadaran Diri Siswa Mengerjakan UKBM - Chairunnisa, Rahmah; Arsini, Yenti (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to test the effectiveness of group counseling with the technique of charting irrational beliefs to increase students' self-awareness in working on UKBM. This study uses a quantitative approach of the pre-experimental type with a one-group pretest- posttest design model. The sample of this study was 7 students of grade XI Social Sciences at MAN 1 Medan. The instrument used was a 30 item Self-Awareness Scale compiled based on Daniel Goleman's theory and the intervention was in the form of group counseling services using the technique of mapping irrational beliefs carried out in 5 meeting sessions, each session lasting 45 minutes. Data analysis techniques used the Wilcoxon test with the help of the SPSS 27.0 application. Based on the results of the Wilcoxon test showing an increase in significance value of 0.018 (p <0.05), it can be concluded that group counseling services with the technique of charting irrational beliefs are effective in increasing self-awareness in students working on UKBM.